2005
DOI: 10.1128/aac.49.6.2429-2437.2005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Efflux Transporters on the Accumulation and Efflux of Four Quinolones (Ciprofloxacin, Levofloxacin, Garenoxacin, and Moxifloxacin) in J774 Macrophages

Abstract: Ciprofloxacin is subject to efflux from J774 macrophages through a multidrug resistance-related protein-like transporter (J. M. Michot, F. Van Bambeke, M. P. Mingeot-Leclercq, and P. M. Tulkens, Antimicrob. Agents Chemother. 48: [2673][2674][2675][2676][2677][2678][2679][2680][2681][2682] 2004). Here, we compare ciprofloxacin to levofloxacin, garenoxacin, and moxifloxacin for transport. At 4 mg/liter, an apparent steady state in accumulation was reached after 30 to 60 min for all quinolones but to quite differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 28 publications
3
89
0
Order By: Relevance
“…This suggests a capacity to rapidly redistribute inside the cell to reach their target, which is consistent with their capacity to easily diffuse through membranes (29) and to their strong binding to the DNA-topoisomerase complex in bacteria (45). In infected cells incubated in neutral medium, delafloxacin shows a very low static concentration and reaches a nearbactericidal effect, making it one of the most active drugs against intracellular S. aureus in this model.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This suggests a capacity to rapidly redistribute inside the cell to reach their target, which is consistent with their capacity to easily diffuse through membranes (29) and to their strong binding to the DNA-topoisomerase complex in bacteria (45). In infected cells incubated in neutral medium, delafloxacin shows a very low static concentration and reaches a nearbactericidal effect, making it one of the most active drugs against intracellular S. aureus in this model.…”
Section: Discussionmentioning
confidence: 57%
“…Fractionation studies were performed with J774 murine macrophages. Both cell lines were maintained in our laboratory as previously described, using RPMI medium supplemented with 10% fetal calf serum (15,29).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Malik and colleagues found that M may be unique among marketed fluoroquinolones in its ability to kill M. tuberculosis in the presence of the protein synthesis inhibitor chloramphenicol (33,34). Improved drug delivery to the site of infection may be an additional reason for the greater potency of M. M concentrates inside macrophages and neutrophils to a greater extent than L (35,36). This may lead to higher exposures for M relative to L in our murine model in which M. tuberculosis resides almost entirely intracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…For each of these antibiotics, the assay method was checked for linearity (telithromycin, 0.03 to 4 mg/liter; azithromycin, 0.05 to 4 mg/liter; ampicillin, 0.21 to 10 mg/liter, nafcillin, 1.1 to 120 mg/liter; oxacillin, 1.6 to 30 mg/liter; penicillin V, 0.04 to 10 mg/liter; rifampin, 0.2 to 15 mg/liter; linezolid, 12 to 190 mg/liter, vancomycin, 2.7 to 150 mg/liter; teicoplanin, 2.9 to 250 mg/liter; gentamicin, 0.6 to 240 mg/liter) and for reproducibility (coefficient of variation, Ͻ10%). Ciprofloxacin, moxifloxacin, and levofloxacin concentrations were measured by fluorimetry (12,56), and garenoxacin and oritavancin concentrations were measured by radiometry by using 14 C-labeled drugs (41,64). In pilot studies we checked that these assays detected genuine, bioactive drug.…”
Section: Methodsmentioning
confidence: 99%